Blood Cell Parameters and Predicting Coronary In-Stent Restenosis. (September 2019) - Wang, Zhichao; Liu, Chi; Fang, Hong
Major advances in coronary interventional techniques and pharmacotherapy as well as the use of drug-eluting stents (DESs) have considerably reduced the risk of in-stent restenosis (ISR). However, ISR remains a major clinical challenge. Inflammation and platelet activation are important processes that underlie the pathophysiology of ISR. Parameters related to blood cells, entailing both cell count and morphology, are useful markers of the inflammatory response and platelet activation in clinical practice. Recent studies have highlighted several new combined or derived parameters related to blood cells that independently predict ISR after DES implantation. The neutrophil/lymphocyte ratio, an inflammatory marker, is regarded as a predictor of the risk of ISR and the stability of atherosclerotic plaques. The mean platelet volume, a widely used platelet activation parameter, has been shown to be a predictor of the risk of ISR and the efficacy of antiplatelet therapy. Other markers considered include the platelet/lymphocyte ratio, red blood cell distribution width, and platelet distribution width. This review provides an overview of these parameters that may help stratify the risk of coronary angiographic and clinical outcomes related to ISR.